Proximal Gastrectomy for Gastric Cancer - Jung, Do Hyun (J Gastric Cancer, 2015)
Laparoscopic proximal gastrectomy (LPG) is theoretically a superior choice of minimally-invasive surgery and function-preserving surgery for the treatment of proximal early gastric cancer (EGC) over procedures such as laparoscopic total gastrectomy (LTG), open total gastrectomy (OTG) and open proximal gastrectomy (OPG). However, LPG and OPG are not popular surgical options due to three main concerns: the first, oncological safety; the second, functional benefits; and the third, anastomosis-related late complications (reflux symptoms and anastomotic stricture). Numerous recent studies have concluded that OPG and LPG present similar oncological safety profiles and improved functional benefits when compared with OTG and LTG. While OPG with modified esophagogastrostomy does not provide satisfactory results, OPG with modified esophagojejunostomy showed similar rates of anastomosis-related late complications when compared to OTG. At this stage, no standard reconstruction method post-LPG exists in the clinical setting. We recently showed that LPG with double tract reconstruction (DTR) is a superior choice over LTG for proximal EGC in terms of maintaining body weight and preventing anemia. However, as there is no definitive evidence in favor of LPG with DTR, a randomized clinical trial comparing LPG with DTR to LTG was recommended. This trial, the Korean Laparoscopic Gastrointestinal Surgery Study-05 (NCT01433861), is expected to assist surgeons in choice of surgical approach and strategy for patients with proximal EGC.